Penerapan Algoritma Stout Codes Untuk Kompresi Databases Pada Pinjaman Online - Rosi Tamala Aini Sitanggang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Along with the development of information and communication technology, the size of a data is sometimes relatively large where the better the quality of the resulting text file, the larger the file size needed to store the text file. With a very large text file size, during the transfer process, the transfer process may fail because the media storage space exceeds the limit. The solution to this problem is how the text file can be compressed in order to speed up the transfer and storage of text files. compression on text files is done by reducing the size of the text file by reducing the bits in the text file, but does not eliminate the information data in it. By compressing, large data will be reduced in size so that it can save storage space. In this study, the algorithm used is Stout codes, by using this algorithm, the compression results from the value of k have different results for each value, and the compression results will benefit in sending, and transferring text files will be easier